Passive wall cooling panel with phase change material as a cooling agent - A. Majid, Masni; Ahmad Tajudin, Rasyidah; Salleh, Norhafizah; Abd. Hamid, Noor Azlina (2017)
The study was carried out to the determine performance of passive wall cooling panels by using Phase Change Materials as a cooling agent. This passive cooling system used cooling agent as natural energy storage without using any HVAC system. Eight full scale passive wall cooling panels were developed with the size 1500 mm (L) x 500 mm (W) x 100 mm (T). The cooling agent such as glycerine were filled in the tube with horizontal and vertical arrangement. The passive wall cooling panels were casting by using foamed concrete with density between 1200 kg/m3 – 1500 kg/m3 . The passive wall cooling panels were tested in a small house and the differences of indoor and outdoor temperature was recorded. Passive wall cooling panels with glycerine as cooling agent in vertical arrangement showed the best performance with dropped of indoor air temperature within 3°C compared to outdoor air temperature. The lowest indoor air temperature recorded was 25°C from passive wall cooling panels with glycerine in vertical arrangement. From this study, the passive wall cooling system could be applied as it was environmental friendly and less maintenance.